Impact of an active hemostatic product treatment approach on bleeding-related complications and hospital costs among inpatient surgeries in the United States. (1st January 2021) - Iannitti, David A.; Kim, Chong; Ito, Diane; Epstein, Josh
Abstract: Aims: To examine the impact of active only (A) vs. combined passive and active (PA) hemostatic products on bleeding-related complications and costs among inpatient surgeries. Materials and Methods: This retrospective analysis of the US Premier Hospital Database included patients who had an inpatient procedure within a specialty of interest (cardiac, vascular, noncardiac thoracic, solid organ, general, reproductive organ, knee/hip replacement, spinal, or neurosurgery) that utilized a hemostatic product from January 1, 2017 to December 31, 2018. Patients were directly matched 1:1 on surgery code, age categories, and Charlson Comorbidity Index score categories into A or PA cohorts. Unadjusted and adjusted rates of bleeding-related complications, length of stay (LOS) and total hospital costs were compared between cohorts. Results: A total of 5, 934 cardiac, 7, 986 vascular, 2, 042 noncardiac thoracic, 8, 260 solid organ, 9, 502 general, 4, 616 reproductive organ, 2, 758 knee/hip replacement, 42, 648 spinal, and 10, 716 neuro surgeries were included. Higher unadjusted rates of bleeding-related complications and greater LOS and total hospital costs were observed in the PA cohort vs A cohort across all specialties. The adjusted odds of bleeding complications were significantly higher in solid organ, general, knee/hip replacement, reproductive organ, and spinal surgery (OR range = 1.17–2.48, all p  <.01), while incremental costs per hospitalization associated with PA (vs A) controlling for covariates were higher across all specialties (ratio range = 1.04–1.22, all p  <.05). Limitations: This analysis focused on patients who had a single surgery during the hospital encounter; results may not be generalizable to patients undergoing multiple surgeries. Conclusions: The use of A hemostatic products was associated with significantly lower rates of bleeding-related complications and total hospital costs compared to PA hemostatic products. A treatment approach which considers bleeding-related factors including severity, risk and variability based on surgery type may provide guidance in choosing the optimal hemostatic product to improve surgical outcomes and costs.